(untitled) (Fiep Bulletin - online, 2015)
Among the humans daily activities is including the act of raising objects, like removing things of the floor, tables and chairs [1]. This act can lead to lumbar injuries depending on the size of the load raised and the distance that the weight if finds of the objective body [2]. The purpose of this study is to observe the electromyographic activity of the lumbar back, in healthy men, during the lifting of weight in two positions; correct and incorrect. The relevance of this work is to investigate the differences between the two movements, to better guide the patients in relation to theirs daily activities. Twenty male volunteers had participated on the study and they all signed the assent term. Electrodes of surface had been adhered in the erector muscle of the spine. The applied load was stipulated in 20% of the total corporal weight of each volunteer, promoting a safe edge for the accomplishment of the movement [3]. Volunteers were positioned in front of a loaded basket on the floor and they had to raise it. Two distinct forms of raising the basket were applied. One form involved the flexion of the knees keeping the back as erect as possible (squat or leg lift)), praised for literature as the correct form. The other involved raising the load with only the movement of bending foward and standing up without moving the knees joint (stoop)[4]. The RMS of the EMG signal was calculated based on the first second of the concentric phase. For analysis statistics of t-student was used the applicatory Statistics version 6.0 with the test, with level of significance of p< 0.05. The electromyographic activation in the muscle analized with level of L3 was significantly lesser during the load rise of correct form (p = 0,009). We suggest new studies with bigger number of volunteers, with both the sexs and different ages, beyond an estimate of the intra-discal pressure through applicatory with models.